A study on the market opportunities of setting up a branch in Tanjung Malim for secondary school students / Yuana Sopian - Sopian, Yuana (1998)
It is definitely important for everybody including the younger generation especially those who are studying to know about computer. This is due to the government's vision to make Malaysia one of the most fast growing country that uses Multimedia Super Corridor (MSC) as their backbone in handling all government and non-government matters. A study on market opportunity of setting up a branch regarding computer centre is being carried out with the intention of helping the company to select the best opportunity for them to at least help the Tanjung Malim secondary student in becoming a computer literate citizen. The main objective of this study is to identify and analyze whether there is opportunity for YZA Computers Sdn. Bhd. to have one of its branches in Tanjung Malim area. Other objectives include determining the level of computer awareness of Tanjung Malim's student. From this study we can see that the students are not well exposed to computer world and their respective school do not have such computer class facilities. Thus there are some opportunities for YZA Computers to set their branch over there but they must also think of their competitors and try to compete their competitors by being different from them for example, having their outlet in colorful building and giving extra services such as scanning that the other competitors do not have. In conclusion, we found out that by being different from the competitors we might lead the computer class market in Tanjung Malim area and be their leader instead of being their follower. However, YZA Computers should take into concern about their financial matters, personnel subject and management in order to success in their new venture in Tanjung Malim.